Associação da sensibilização central com a intensidade da dor e a atividade eletromiográfica do musculo trapézio descendente de indivíduos com cervicalgia idiopática crônica - Melo, Nivea Cristina de (2020)
Introduction: Central sensitization is one of the occasional phenomena due to a malfunction of descending anti-nociceptive mechanisms that is generally correlated with chronic diseases among them that cause neck pain, which frequently affects the population and becomes a constant headache and of physical origin and psychological. Objectives: To verify correlations between central sensitization and pain intensity and electromyographic activity of the trapezius muscle in individuals with chronic non-specific neck pain. Methods: Cross-sectional study, consisting of a sample of 25 individuals aged between 18 and 45 years old who presented neck pain index (NDI) between 10 and 24 points and pain between 3 and 10, measured by the numerical pain assessment scale (ENAD). The volunteers were selected according to the following requirements: Central Sensitization Inventory (ISC), Pain Catastrophization Scale, NDI, Pain: assessed by ENAD and Algometry in three pre-selected tests on the TFD muscle and two discs (anterior tibial tension and sternum mannequin) and electromyographic activity (EMG) of the TFD muscle considering three strength levels corresponding to 10, 20 and 30% of the calculated CVM (maximum voluntary contraction). Results: The variable ISC has a strong correlation with the NDI (r = 0.73, p <0.01) and a moderate correlation with algometry of the retained muscles (r = -0.41, p <0.05), AT (r = -0.46, p <0.05) and with the external mannequin (r = -0.46, p <0.05) as a catastrophization (r = 0.51, p <0.05). The NDI also showed a moderate correlation with catastrophization (r = 0.68, p <0.01). Regarding the EMG signal, no association was found with other measures of clinical outcome. Conclusions: In this study, there was no association between central sensitization and pain intensity and electromyographic activity of the descending trapezius muscle in individuals with chronic idiopathic neck pain. However, an association of central sensitization with catastrophization and neck disability index was observed.